Qualitative Classification of Shear Wave Elastography for Differential Diagnosis Between Benign and Metastatic Axillary Lymph Nodes in Breast Cancer - Luo, Shuyi; Yao, Guangyu; Hong, Zhe; Zhang, Shiyu; Wang, Weizhen; Zhang, Jingwen; Zhang, Yaru; Wu, Junkai; Zhang, Li; Cheng, Hong; Hao, Yi; Li, Yingjia (Frontiers in Oncology, 2019)
Purpose To examine diagnosis performance of qualitative shear wave elastography (SWE) for evaluation of status of axillary lymph nodes (ALN), and to compare diagnosis performances of this method with conventional ultrasonograghy (US) and quantitative SWE parameters. Methods A total of 121 ALNs from 118 patients were enrolled, who were all scheduled for breast cancer surgery and core needle biopsy. Conventional US and SWE were performed before biopsy. Each ALN was evaluated by a qualitative classification method to classify the SWE images into four color patterns: Color Pattern 1: homogeneous; Color Pattern 2: filling defect within lymph node (LN); Color Pattern 3: homogeneous within LN with a localized colored area at the margin; and Color Pattern 4: filling defect within LN with a localized colored area at the margin. The diagnostic performances of the three methods were compared. Results There were 60 metastatic nodes and 61 benign nodes in the 121 ALNs. Benign ALNs presented as Color Pattern 1 while metastatic ALNs usually presented as Color Pattern 2 to 4 (p<0.05). The AUC of qualitative SWE classification was 0.983, exceeding that of quantitative SWE parameters and conventional US (p<0.05). The combined conventional US and qualitative SWE classification revealed the highest diagnostic performance, with AUC of 0.998. Conclusion The qualitative SWE classification of ALNs proposed in our study exhibited better diagnostic performance than quantitative SWE parameters and conventional US, especially for differentiating diagnosis of metastatic ALNs from benign reactive ALNs. This new method could achieve more accurate diagnosis and avoid unnecessary biopsy.